Competing with injuries: injuries prior to and during the 15th FINA World Championships 2013 (aquatics). Issue 1 (17th October 2014) - Mountjoy, Margo; Junge, Astrid; Benjamen, Sarah; Boyd, Kevin; Diop, Mohamed; Gerrard, David; van den Hoogenband, Cees-Rein; Marks, Saul; Martinez-Ruiz, Enrique; Miller, Jim; Nanousis, Kyriakos; Shahpar, Farhad Moradi; et al.
Abstract : Background: Injury and illness surveillance is the foundation for the development of prevention strategies. Objective: To examine injuries among the aquatic disciplines in the 4 weeks prior to and during the 2013 FINA World Championships. Methods: The study was comprised of two components: (1) a retrospective athlete survey recording injuries in the 4 weeks prior to the Championships and (2) a prospective recording of injuries and illnesses by the medical teams of the participating countries and the local host medical team. Results: One-third of the 1116 responding athletes reported an injury/physical complaint in the 4 weeks prior to the Championships. Significantly more women (36.7%) than men (28.6%) reported injuries. Divers reported the highest rate of injury/physical complaints (55.7%). At the start of the Championships, 70% of injured respondents (n=258) were still symptomatic; however, full participation was expected by 76%. During the Championships, 186 new injuries were reported (8.3/100 registered athletes) with the highest injury incidence rate in water polo (15.3/100 registered athletes). The most common injured body part was the shoulder (21%). A total of 199 illnesses were reported during the Championships (9.0/100 registered athletes) with the most common diagnosis of illness being gastrointestinal infection. Environmental exposure (allergy, otitis and jellyfish stings) was responsible for 27% of all illnesses in open water swimming. Conclusions: Injuries pose a significant health risk for elite aquatic athletes. A prospective study would improve understanding of out-of-competition injuries. Future injury and illness surveillance at FINA World Championships is required to direct and measure the impact of prevention strategies.